KAIDAH-KAIDAH PENATAAN RUANG DALAM RANGKA PENGELOLAAN LINGKUNGAN (Kajian Yuridis) - Agus Widodo (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2020)
Spatial planning is aimed at realizing harmony between the natural environment and the artificial environment, the integrated use of natural resources and artificial resources. Spatial planning is also intended to protect the function of space and environmental preservation. According to Law No. 26 of 2007 concerning Spatial Planning, space is based on all interests in an integrated, efficient and effective, harmonious, harmonious and balanced manner. The problem formulation in this study is How are the rules of spatial planning in the framework of environmental management? The first rule that must be held in spatial planning for development is that every change must be better than the previous day, namely a more prosperous, comfortable future without the fear of anxiety and fear of various phenomena, such as an unhealthy living environment because of unclear spatial planning. , natural disasters due to the blind use of natural resources and other actions without planning, without arrangement and others. The second principle in spatial planning is to do explicit territory in the long term or be thankful forever without change, because many spatial arrangements are so easy to change and only obey the wishes of the market or capital owners. Now we see a lot of productive agricultural land, productive plantation land, forests cleared to meet the demand of the market turned into industrial buildings, housing, and even green open space (RTH) and city parks turned into malls.